Telomere length is a critical determinant for survival in multiple myeloma - Hyatt, S; Jones, R; Heppel, N; Grimstead, J; Fegan, C; Jackson, G; Hills, R; Allan, J; Pratt, G; Pepper, C; Baird, D (Wiley, 2017)
The variable clinical outcomes of Multiple Myeloma (MM) patients are incompletely defined by current prognostication tools. We examined the clinical utility of high-resolution telomere length analysis as a prognostic marker in MM. Cohort stratification, using a previously determined length threshold for telomere dysfunction, revealed that patients with short telomeres had a significantly shorter overall survival (P < 0·0001; HR = 3·4). Multivariate modelling using forward selection identified International Staging System (ISS) stage as the most important prognostic factor, followed by age and telomere length. Importantly, each ISS prognostic subset could be further risk-stratified according to telomere length, supporting the inclusion of this parameter as a refinement of the ISS.